FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT BERWIRAUSAHA MAHASISWA MENGGUNAKAN THEORY OF PLANNED BEHAVIOR (Studi pada Mahasiswa Pelaku Wirausaha Fakultas Ekonomika dan Bisnis Universitas Diponegoro) - Sukmaningrum, Swastinitya; Rahardjo, Mudji (Diponegoro Journal of Management, 2017)
This research aims to examines the factors that effect the entrepreneurial intention of the students in the Faculty of Economics and Business in Diponegoro University. Related to the vision, mission and the objectives of the Faculty of Economics and Business in Diponegoro University, i.e. develop an academic community life which has the entrepreneurial soul on entire campus residents supported by scientific culture of faith and pious to Almighty God.The  population  in  this  research  is  the  students  in  eight  semester  of  the  Faculty  of Economics  and  Business  in  Diponegoro  University.  The sampling  technique  which  used  is proportional stratified sampling with the total sample 69 students. The analysis tool which used is multiple linear regression thus has tested the validity and reliability first. The analysis is used to examines the influence of self-efficacy, subjective norms, need for achievement, and parental background on the intention of entrepreneurship.The  results  shows  that  the  self-efficacy,  subjective  norms,  need  for  achievement,  and parental background on the intention of entrepreneurship, are the influential factors that have a positive effect either partially or simultaneously. While the need for achievement is a factor that has the most impact in comparison with other factors. Another factor affecting student’s entrepreneurial intention is a subjective norm. Thus, the individuals who want to be an entrepreneurs, make sure that they will be supported by the surrounding people (family, close friends, and other important people) and can accept the suggestions and criticism from others to be better than the other.